2017
DOI: 10.1007/s00405-017-4646-0
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of tongue base masses in children by transoral robotic surgery

Abstract: The feasibility and effectiveness of transoral robotic surgery (TORS) in children with tongue base masses (TBMs) were evaluated. Eight pediatric patients who were treated with TORS for TBMs between January 2010 and January 2016 at a tertiary hospital included in the study. All pathologies were congenital lesions: four were lingual thyroglossal ductus cysts (LTGDCs), one was a minor salivary gland tumor, one was a vallecular cyst, one was a bronchogenic cyst, and one was an ectopic thyroid tissue. TORS was perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 25 publications
0
16
0
1
Order By: Relevance
“…On intraoperative blood losses, only eight studies reported these data (5, 7, 8, 10-12, 15, 18), and in all cases, it was < 25 ml, except one subject < 50 ml (15).…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…On intraoperative blood losses, only eight studies reported these data (5, 7, 8, 10-12, 15, 18), and in all cases, it was < 25 ml, except one subject < 50 ml (15).…”
Section: Resultsmentioning
confidence: 98%
“…The second most performed surgery was laryngeal cleft repair treating 18 subjects (1,8,9,12). The third most common intervention (7 subjects) was the exeresis of lingual thyroglossal duct cyst (6,11,15,17). Neoplastic pathology was treated in six subjects (8, 21%), four of these with malignant disease of the base-tongue: three sarcomas (4, 5, 14) and one minor salivary gland tumor (15).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[11] Son dönemde transoral robotik cerrahi yöntemini kullanarak pediatrik dil kökü kitlelerinde (lingual triglossal duktus kisti, valleküler kist, bronkojenik kist gibi) başarılı sonuçlar elde eden Kayhan ve ark. [12] ileride robotik cerrahinin pediatrik dil kökü kitlelerinde standart tedavi yöntemi olabileceğini vurgulamışlardır.…”
Section: Discussionunclassified
“…Open surgery can facilitate access to the oropharyngeal region, including the base of the tongue, but can lead to the morbidity of splitting the lip and jaw or require pharyngotomy. As a result, the robotic transoral approach is being used [165]. In the near future, we believe that transoral robotic surgery may become the gold standard.…”
Section: Otorhinolaryngologymentioning
confidence: 99%